The role of Adjust Resources Fund in financing the Public budget deficit in Algeria over the period 2000-2019 - برودي نعيمة (Milev Journal of Research and Studies, 2020)
This study aims to show the importance of sovereign wealth funds to benefit from saving from oil revenues and use them in the event of public budget deficit. many developing and developed countries are faced with the problem of a public deficit, which means that general spending exceeds general incomes. This study aimed to present Algeria's experience by establishing Revenue Adjustment fund to finance the deficit in the public finances and repayment of foreign debt.